Halecium arcticum (Cnidaria: Hydrozoa), a new species of hydroid from Spitsbergen - Ronowicz, Marta; Schuchert, Peter (Zootaxa, 2007)
A new species of the genus Halecium is described and figured. The new species was found among the kelp forest-associated fauna collected during the Polish diving expedition to Hornsund (Spitsbergen, Svalbard Archipelago) in 2003. The relationships with several closely-related Halecium species are discussed.